-6x-5y=-27

Simple and best practice solution for -6x-5y=-27 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for -6x-5y=-27 equation:


Simplifying
-6x + -5y = -27

Solving
-6x + -5y = -27

Solving for variable 'x'.

Move all terms containing x to the left, all other terms to the right.

Add '5y' to each side of the equation.
-6x + -5y + 5y = -27 + 5y

Combine like terms: -5y + 5y = 0
-6x + 0 = -27 + 5y
-6x = -27 + 5y

Divide each side by '-6'.
x = 4.5 + -0.8333333333y

Simplifying
x = 4.5 + -0.8333333333y

See similar equations:

| 4X+5=2(-2X+4) | | -24=5g+15 | | -7m+9=26-2m | | 2(X+5)+6X=-27 | | -3x^2+18x=34 | | 3(h+8)=-18 | | 4X+5=-4X+6 | | 5x-(6x+6)=3x-50 | | 2(d-10)+2=-8 | | y+10x=8 | | 2(y+1)-15=5 | | 24x^4y+21x^3= | | 10(5+W)=-3(W+5) | | 2-4x=5x+20 | | 2030+5x=-15 | | -15k-7k+-10=12 | | 1/38=2.25/x | | 7/3-7i | | 5x-31=x+5 | | 9x+27x^2= | | -12n+16n+-19=-13 | | -3a+8b+61=0 | | 27.00/2.25 | | 1/38=5.5/x | | 2(c-8)+-6=8 | | -2x+3(x-3)=-13 | | 11=-5x+21 | | a^4+8=11 | | 6-7x=5x-10x+8 | | 3x+4=-39 | | 10=2(c+1)+2 | | 7(3x-2)=5(2x-1) |

Equations solver categories